Electron-transfer-initiated cascade cyclizations of terpenoid polyalkenes in a low-polarity solvent: One-step synthesis of mono- and polycylic terpenoids with various functionalities - Ozser, ME; Icil, H; Makhynya, Y; Demuth, M (Wiley-V C H Verlag Gmbh, 2004)
A methodology for the one-step synthesis of cyclic polyalkene terpenoids in a low-polarity solvent (dichloromethane) by photoinduced electron transfer (PET) is described. For the efficiency of such processes in low-polarity solvents, the use of the cationic electron acceptor N-methylquinolinium. hexafluorophosphate is vital. The first direct cyclizations of farnesol and geranylgeraniol to the corresponding all-trans-fused 6,6- and 6,6,6-cyclic products are also reported. The mechanism of the termination of the cyclizations is also discussed, isotope-labeling experiments having shown that it proceeds through reduction of the final radical to the corresponding anion, followed by protonation. ((C) Wiley-VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany, 2004).
Keywords: biomimetic synthesis; photo-induced electron transfer; polyene cascade cyclization; radical cation; terpenoids